2009
DOI: 10.1016/j.chemosphere.2009.01.006
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary investigation on emission of polychlorinated dibenzo-p-dioxins/dibenzofurans and dioxin-like polychlorinated biphenyls from coke plants in China

Abstract: a b s t r a c tThermal related processes are widely recognized as the main sources of formation and emission of polychlorinated dibenzo-p-dioxins/dibenzofurans (PCDD/Fs) and polychlorinated biphenyls (PCBs). It is well known that, carbonization of coal in coke production involves many thermal reactions at high-temperature. However, there are still no strong evidences to identify coking processes as source of PCDD/Fs and PCBs. In this study, coke production was qualified and quantified for emission of PCDD/Fs a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 18 publications
0
13
0
3
Order By: Relevance
“…These properties make it possible for PCBs to undergo long-range transport, and they pose global risks to human health and the environment (Liu et al 2009a;Meijer et al 2003;Ren et al 2007). The manufacture and use of commercial products containing PCBs were banned in most countries in 1973.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These properties make it possible for PCBs to undergo long-range transport, and they pose global risks to human health and the environment (Liu et al 2009a;Meijer et al 2003;Ren et al 2007). The manufacture and use of commercial products containing PCBs were banned in most countries in 1973.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, unintentional emissions of PCBs during industrial thermal processes have been becoming, and will continue to become, more important sources of PCBs in the environment. These thermal emission sources of PCBs include iron sintering, secondary nonferrousmetal smelting, iron casting, coking, and converter steelmaking; iron-ore sintering is an important industrial source of PCBs (Ba et al 2010;Ba et al 2009;Li et al 2014;Liu et al 2009a;Liu et al 2009b;Luthardt et al 2002;Lv et al 2011;Tian et al 2012). The environmental presence and behaviors of PCBs have been studied for more than 30 years (Li et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…e l s e v i e r . c o m / l o c a t e / s c i t o t e n v (Liu et al, 2009). However, concerns about their persistent and toxic nature led to their ban throughout the world in the late 1970s .…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%
“…The emission factor of 3 mg I-TEQ ton À 1 for air has been applied to coke facilities where no dust removal device is in use (UNEP, 2005). Recently, Liu et al (2009) identified that there was a large variance of PCDD/F emissions among three coke plants due to the differences of the coking techniques and end-of-pipe control devices used. The PCDD/Fs released in mixed emitted gases from charging of coal and the pushing of coke at a coke plant with an annual production capacity of 200 thousand tons was 1697.7 pg WHO-TEQ Nm À 3 .…”
Section: Reduction Of Pcdd/f Emissions To Air In the Coke Industrymentioning
confidence: 99%